Using a Geosocial Networking App to Investigate New HIV Infections and Related Risk Factors Among Student and Nonstudent Men Who Have Sex With Men in Chengdu, China: Open Cohort Study - Zhen Dai; Guodong Mi; Fei Yu; Guodong Chen; Xiaodong Wang; Qinying He (JMIR Publications, 2023)
BackgroundIn China, condomless sex among men who have sex with men (MSM) is the primary route of HIV infection in young people. Chengdu is a hotspot for reported HIV cases among young people nationwide. Extensive use of geosocial networking (GSN) smartphone apps has dramatically changed the pattern of sexual behavior among young MSM (YMSM). However, data on HIV incidence and the risk behavior of YMSM using the GSN app are still obscure. ObjectiveThis study aims to analyze and understand the HIV incidence and its risk factors among YMSM using GSN apps in Chengdu, China. MethodsAn open cohort study was conducted among YMSM aged 18-24 years through a gay GSN smartphone app in Chengdu, China, from July 2018 to December 2020. Every participant completed a web-based questionnaire on sociodemographic characteristics, sexual behaviors, and other related statuses; made a reservation for a web-based HIV testing; and then voluntarily got tested at the designated testing site. At least one additional HIV test was taken via the app during the study period, and participants were evaluated at the end of the study or at the time of HIV seroconversion. By dividing the sum of the observed HIV seroconversions by the observed person-years, HIV incidence was calculated and compared between the student and nonstudent MSM. Univariate and multivariate (Cox proportional hazards regression) analyses were used to discuss the risk factors for new HIV infections. ResultsIn the study cohort, 24 seroconversions occurred among 625 YMSM who took at least two HIV tests through the app during the study period, contributing to 505 observed person-years. The HIV incidence rate per 100 person-years was 4.75 (95% CI 2.89-6.61) among all MSM, 3.60 (95% CI 1.27-5.93) among student MSM, and 5.88 (95% CI 2.97-8.79) among nonstudent MSM. In addition, the HIV incidence per 100 person-years was 11.11 (95% CI 4.49-17.73) among those who had resided in the area for 6 months or less and 7.14 (95% CI 1.52-12.77) among those with senior high school or less education. Two or more sexual partners (adjusted hazards ratio [HR] 3.63, 95% CI 1.08-12.23) in the preceding 6 months was a risk factor for new HIV infections. Consistent condom use for anal sex (adjusted HR 0.38, 95% CI 0.16-0.88) and insertive anal sex only (adjusted HR 0.10, 95% CI 0.01-0.75) in the preceding 6 months were protective factors for new HIV infections. ConclusionsThe rate of new HIV infections among YMSM who actively used GSN smartphone apps was high, especially among migrant nonstudent MSM. Targeted interventions on GSN smartphone apps should be implemented to provide demand-adapted prevention and services to reduce the threat of HIV.